Theory of mind, emotional and social functioning, and motor severity in children and adolescents with dystonic cerebral palsy. (May 2017) - Adegboye, Dolapo; Sterr, Annette; Lin, Jean-Pierre; Owen, Tamsin J.
Abstract: Aims: This cross-sectional study aimed to investigate whether children and adolescents with dystonic cerebral palsy (CP) present with emotional and social difficulties along side motor limitations. Participants/measures: Twenty-two verbal and nonverbal children and adolescents with dystonic CP were compared with a normative sample of twenty children and adolescents on measures of theory of mind (ToM), emotion regulation (ER), and social difficulties (SD). Results: Higher social and emotional difficulties were found in the dystonic CP group compared to the control group. Nonverbal participants with dystonic CP were found to present with greater social impairment and lower ToM ability than their verbal counterparts. Emotional regulation and hyperactivity and attentional difficulties (HAD) significantly predicted ToM ability and social difficulties. Lower Gross Motor Function Classification System (GMFCS) level and IQ also contributed to differences in ToM ability. Interpretation: Findings support the need for greater attention to the emotional health and social development of children/adolescents with dystonic CP, along with assessments of motor difficulties in the planning and implementation of interventions and individual care plans. Further research is needed to explore links between motor disorder and mental state understanding in this clinical group. Highlights: The psychological functioning of young people with dystonic CP is often overshadowed by a focus on their motor limitations. A significant number of young people with dystonic CP have difficulties with both ToM and social communication. Inability to regulate emotions and attentional difficulties influence the relationship between ToM and social difficulties.